2018
DOI: 10.1177/0391560318802160
|View full text |Cite
|
Sign up to set email alerts
|

Tribulus terrestris versus placebo in the treatment of erectile dysfunction and lower urinary tract symptoms in patients with late-onset hypogonadism: A placebo-controlled study

Abstract: Aging is associated with a series of morphological and functional modifications that leads to reduced physiological efficiency and atrophy of various organs and systems. Tribulus terrestris induces its effect in fertility and sexual functions through the steroidal saponins, particularly the dominant saponins protodioscin. We aimed in this study to evaluate the efficacy and safety profiles of Tribulus terrestris in aging males with partial androgen deficiency who suffered from erectile dysfunction and lower uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…At the same time, ICP and ICP/MAP records of the rats in this study also showed that the erectile function of the mixed treatment group significantly improved compared with the T2DMED group, the GSTT-only group, or the sildenafil-only group. This confirms previous studies on GSTT in basic and clinical trials to improve erectile function 2528. We further found that GSTT can improve the expression of eNOS in rat endothelial cells, directly increasing the concentration of NO, and ultimately improving the level of cGMP in each group.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, ICP and ICP/MAP records of the rats in this study also showed that the erectile function of the mixed treatment group significantly improved compared with the T2DMED group, the GSTT-only group, or the sildenafil-only group. This confirms previous studies on GSTT in basic and clinical trials to improve erectile function 2528. We further found that GSTT can improve the expression of eNOS in rat endothelial cells, directly increasing the concentration of NO, and ultimately improving the level of cGMP in each group.…”
Section: Discussionsupporting
confidence: 91%
“…Tribulus terrestris was investigated as a single herb in two of the included studies, both using standardised extractions for saponins and reporting a positive effect on the IIEF and various domains [ 37 , 38 ]. Furthermore, with Tribulus terrestris as the major constituent, the combination formulae Tradamix TX1000, VXP, and NRL/MW/201,901 were also shown to increase IIEF and all domains [ 29 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (39,48,54,61) examined the effects of Tribulus terrestris on testosterone concentrations. Two studies used patented extracts, Trib Gold, manufactured by Nerhadou International, standardized to contain up to 45% steroidal saponins (extract source not provided) (39), and Tribestan, manufactured by Sopharma, delivering a minimum of 675 mg furostanol saponins (from overground parts of the herb) (48). Santos et al (61) and Neychev and Mitev (54) both used a dry extract of tribulus.…”
Section: Tribulus Terrestris (Tribulus)mentioning
confidence: 99%
“…Santos et al (61) and Neychev and Mitev (54) both used a dry extract of tribulus. Three studies were randomized controlled trials (39,48,54) and 1 study was a randomized, double-blind, placebo-controlled trial (61). A total of 301 participants were recruited for the studies involving Tribulus terrestris, with ages ranging from 18 to 65 y and sample sizes ranging from 21 to 180 participants.…”
Section: Tribulus Terrestris (Tribulus)mentioning
confidence: 99%